THE CHARACTERISTICS LEVEL OF MATERNAL SATISFACTION IN RECEIVING ANTENATAL CARE (ANC) - Rosa Mutianingsih; Siti Mardiningsih (International Journal of Midwifery Research, 2022)
The low working capacity of puskesmas midwives in health care facilities is one indicator of low work effectiveness, as well as service satisfaction for pregnant women . The purpose of this study was to identify the level of maternal satisfaction about obstetric examination services antenatal care (ANC) by health workers at Karang Pule Health Center. Research design using descriptive survey research methods . the population, namely all pregnant women who did ANC at the Karang Pule Health Center in January to June 2020, was 96 people. Sampling technique Accidental sampling. Number of samples as many as 30 respondents, how to process data using Likert scale. From the results showed that the level of maternal satisfaction in the acceptance of ANC examination services in general from the aspect of Tangibles, expressed satisfaction as many as 23 respondents (76.67%), Reliability expressed satisfaction as many as 23 respondents (76.67%), Responsivenes expressed satisfaction as many as 24 respondents (80%), assurance expressed satisfaction as many as 22 respondents (73.33%),Emphaty expressed satisfaction as many as 24 respondents (80%), the results of this study concluded 78, 38% expressed satisfaction. It is expected from the results of this study to be one of the inputs on the need to improve the attention and standards of ANC services in health centers